2013
DOI: 10.1038/ncomms2344
|View full text |Cite
|
Sign up to set email alerts
|

Kinship reduces alloparental care in cooperative cichlids where helpers pay-to-stay

Abstract: Alloparental brood care, where individuals help raising the offspring of others, is generally believed to be favoured by high degrees of relatedness between helpers and recipients. Here we show that in cooperatively breeding cichlids, unrelated subordinate females provide more alloparental care than related ones when kinship between dominant and subordinate group members is experimentally manipulated. In addition, unrelated helpers increased alloparental care after we simulated egg cannibalism by helpers, an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
120
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(139 citation statements)
references
References 57 publications
(126 reference statements)
10
120
0
Order By: Relevance
“…Thus, it appears that in N. pulcher, the major function of subordinates' cooperation with dominants is the enhancement of their chances to survive and reproduce later, rather than direct or indirect fitness gains during their helper stage. A crucial component of this pattern is the pay-to-stay mechanism [50,51], by which subordinates trade help for access to shelters and protection provided by dominants [7,52]. An increased cost of membership in larger groups may thus explain the absence of positive fitness effects of large group size [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it appears that in N. pulcher, the major function of subordinates' cooperation with dominants is the enhancement of their chances to survive and reproduce later, rather than direct or indirect fitness gains during their helper stage. A crucial component of this pattern is the pay-to-stay mechanism [50,51], by which subordinates trade help for access to shelters and protection provided by dominants [7,52]. An increased cost of membership in larger groups may thus explain the absence of positive fitness effects of large group size [39].…”
Section: Discussionmentioning
confidence: 99%
“…due to improved survival chances when delaying reproduction) [1,5]. Several mechanisms by which direct fitness benefits may be reaped from cooperation have been proposed, including reciprocity [6], commodity trading [7], benefits from queuing for high-quality resources [8] and group augmentation [9]. A key aspect of direct benefits of cooperation in group-living animals is that group membership yields higher fitness than solitary life [9].…”
Section: Introductionmentioning
confidence: 99%
“…B 371: 20150090 models support the hypothesis that generalized reciprocity can create evolutionarily stable levels of cooperation in a Prisoner's Dilemma situation by the simple decision rule of 'help anyone if helped by someone', and that following these rules need not be cognitively demanding [105,106]. Although empirical evidence for reciprocal cooperation in natural, non-captive settings still lags behind theory, recent studies on alloparental care have convincingly interpreted helping behaviour by non-relatives as a type of commodity trading-essentially, that helpers 'pay to stay' in the social group by providing cooperative services [57,59].…”
Section: (B) Reproduction By Subordinatesmentioning
confidence: 99%
“…A similar lack of kinship effect has also been demonstrated in three independent experiments of artificially formed groups of African cichlids, Neolamprologus pulcher (Stiver et al, 2005;Le Vin et al, 2011;Zöttl et al, 2013). All three studies compared groups of cichlids under laboratory conditions where helpers were either related or unrelated to an adult pair and showed that kinship was not related to the amount or type of help that subordinates performed.…”
Section: Monogamy and Kinshipmentioning
confidence: 57%
“…While these findings may appear to contradict kin selection based models, it is possible that related and unrelated helpers are provisioning help for different reasons. Le Vin et al (2011) Stiver et al (2005 and Zöttl et al (2013) all pointed out that related helpers may help their relatives in order to receive indirect genetic benefits while unrelated helpers may have to "pay to stay" (i.e., provide help to avoid eviction) in order to enjoy the direct fitness benefits of group living (see Quiñones et al, 2016 for a model based on this species showing that negotiations in a pay to stay scenario can result in higher levels of cooperation than relatedness). These studies highlight the importance of using experimental studies to demonstrate causality of effects described using observational data.…”
Section: Monogamy and Kinshipmentioning
confidence: 99%